Pragmatic Adaptation in Film Translation: Strategies for Achieving Adequacy in Modern Cinema Discourse - Ahmedova, Mohigul Muzaffar qizi (The Lingua Spectrum, 2026)
This article explores pragmatic adaptation in film translation as an essential tool for achieving adequacy in modern cinema discourse. The study focuses on how translators preserve communicative intention, emotional impact, humor, and cultural meaning while transferring audiovisual materials from one language into another. Particular attention is paid to linguistic and cultural challenges, including slang, idioms, culture specific references, and sociolects that may create barriers for target audiences. The research analyzes major adaptation strategies such as domestication, localization, substitution, omission, and compensation, which allow translators to produce natural and understandable dialogues. The article also emphasizes the importance of intercultural competence and contextual awareness in audiovisual translation. The findings show that pragmatic adaptation improves the quality, authenticity, and audience perception of translated films, ensuring effective cross-cultural communication in the rapidly developing global film industry and contemporary digital media environment. The study contributes to current research on translation theory and audiovisual communication.